The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1016/j.jfludis.2013.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral inhibition and childhood stuttering

Abstract: Purpose The purpose of this study was to assess the relation of behavioral inhibition to stuttering and speech/language output in preschool-age children who do (CWS) and do not stutter (CWNS). Method Participants were preschool-age (ages 36 to 68 months), including 26 CWS (22 males) and 28 CWNS (13 males). Participants’ behavioral inhibition (BI) was assessed by measuring the latency to their sixth spontaneous comment during conversation with an unfamiliar experimenter, using methodology developed by Kagan, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
78
2
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 61 publications
(84 citation statements)
references
References 39 publications
2
78
2
1
Order By: Relevance
“…T here has been considerable empirical study of, as well as speculation regarding, the possible relation between emotion and childhood stuttering (e.g., Adams, 1992;Bloodstein, 1949;Choi, Conture, Walden, Lambert, & Tumanova, 2013;Conture, Kelly & Walden, 2013;Guitar, 2014;W. Johnson et al, 1959;Jones, Choi, Conture, & Walden, 2014;Yairi, 1997).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…T here has been considerable empirical study of, as well as speculation regarding, the possible relation between emotion and childhood stuttering (e.g., Adams, 1992;Bloodstein, 1949;Choi, Conture, Walden, Lambert, & Tumanova, 2013;Conture, Kelly & Walden, 2013;Guitar, 2014;W. Johnson et al, 1959;Jones, Choi, Conture, & Walden, 2014;Yairi, 1997).…”
mentioning
confidence: 99%
“…For example, Choi et al (2013) reported that CWS with high behavioral inhibition stuttered more than CWS with low behavioral inhibition. similarly reported that CWS's negative emotional behaviors (e.g., frowning, crying, etc.)…”
mentioning
confidence: 99%
“…Data were previously collected as part of an ongoing series of empirical investigations of linguistic and emotional associates of childhood stuttering conducted by Vanderbilt University's Developmental Stuttering Project (e.g., Arnold, Conture, Key, & Walden, 2011;Choi, Conture, Walden, Lambert, & Tumanova, 2013;Clark, Conture, Frankel, & Walden, 2012;Johnson, Walden, Conture, & Karrass, 2010;Jones et al, 2014;Millager et al, 2014;Richels et al, 2010;Walden et al, 2012). Children were paid volunteers whose caregivers learned of the study from (a) a free monthly parent magazine circulated throughout middle Tennessee, (b) a local health care provider, or (c) self-or professional referral to the Vanderbilt Bill Wilkerson Hearing and Speech Center for an evaluation.…”
Section: Participantsmentioning
confidence: 99%
“…Recent studies suggest a continued interest among researchers in the relationship between stuttering and temperament in children [1][2][3][4][5][6]. Findings complement others in suggesting differences in specific aspects of temperament (e.g., emotion reactivity, emotion regulation, attention regulation, behavioral inhibition) between children who stutter (CWS) and children who do not stutter (CWNS) or differences among sub-groups of CWS based on age or other characteristics of stuttering (e.g., disfluency type, presence of secondary behaviors) [1,[7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies report differences based on behavioral observation, many employ methodology primarily based on parentreport in which the parent(s) completes a questionnaire detailing their account of their child's temperament [2,4,5,[11][12][13][14][15]. Prior to discussing these research studies in more detail, first we will consider a definition of temperament.…”
Section: Introductionmentioning
confidence: 99%